Pengaruh Latihan Menggunakan Ringhoop Terhadap Ketepatan Tendangan Pada Ekstrakurikuler Futsal Smp Negeri 30 Palembang - Muhammad Redho Arbain Arbain; Aprizal Fikri; Bayu Hardiyono; I Bagus Hendrawan (Universitas Negeri Padang, 2025)
Does kicking technique training play an important role? In futsal, kicking techniques are very important to help player concentration and create opportunities and the ability to direct the ball into the goal as desired. In this study, the aim is to determine the effect of training using a ring hoop on kicks in futsal extracurricular students at SMP Negeri 30 Palembang. The method used is an experiment with a one-group pretest-posttest design. The sample consisted of 20 students who actively participated in futsal extracurricular activities. The instrument or tool used in this study was a test with a kick accuracy test. The results of the analysis showed that at the stages of data normality testing, homogeneity testing and t-testing. Based on the findings of this study, it was obtained that t count 6.962> t table 2.093, with a significance value of 0.000 <0.05. It can be concluded that training using a ring hoop has a positive effect on increasing students' kick accuracy in futsal games at SMP Negeri 30 Palembang.